DNA MICROARRAY ANALYSIS OF GENES INVOLVED IN THE PROCESS OF DIFFERENTIATION IN MOUSE LEYDIG CELL LINE TTE1 - Ohta, S.; Fuse, H.; Tabuchi, Y. (Archives of andrology, 2002)
A Leydig cell line, TTE1, was established from the temperature-sensitive simian virus 40 large T-antigen transgenic mice. The cells showed temperature-sensitive growth characteristics and a differentiated phenotype at a nonpermissive temperature. To identify differentially expressed genes in the process of Leydig cell differentiation, the authors carried out microarray analysis of TTE1 cells cultured at permissive and nonpermissive temperatures. The resulting fluorescence-labeled cDNAs synthesized from mRNAs were hybridized with Clontech's Atlas glass mouse 1.0 microarrays. Of the 1081 genes analyzed, the levels of 31 genes were changed, with 24 genes showing increased levels of expression and the remaining 7 genes showing decreased levels. Tie2 was the most changed transcript, with a 13.5-fold upregulation under the differentiated condition. The authors believe this to be the first report of broadscale gene expression in Leydig cell differentiation using the microarray technology. The ability to analyze broadscale gene expression in this manner provides a powerful tool for investigating the molecular mechanisms of Leydig cell functions.